Two new species of hermit crabs of the genus Areopaguristes Rahayu & McLaughlin, 2010 (Crustacea: Anomura: Paguroidea: Diogenidae) from the eastern tropical Pacific - Ayón-Parente, Manuel; Hendrickx, Michel E. (Zootaxa, 2012)
The genus Areopaguristes Rahayu & McLaughlin, 2010 is represented in the eastern Pacific by a single species, A.mclaughlinae (Ayón-Parente & Hendrickx, 2006). Based on material recently collected in the Gulf of California, Mexico,and held in museum collections, two new species of this genus are described. Areopaguristes lemaitrei sp. nov. and A.waldoschmitti sp. nov. Both have the typical 12 gills of the genus. In addition to its color pattern, A. lemaitrei sp. nov. isdistinguished by the presence of corneous-tipped spines on palm and fingers, a broadly rounded rostrum shorter than lat-eral projections, and by the shape of the external lobe of the first pleopod. Areopaguristes waldoschmitti sp. nov. also fea-tures a distinctive color pattern, a less spinous armature of chelipeds, antennular peduncles proporcionally longer andantennal acicle shorter, a deep median cleft on the posterior margin of telson, and the distal margin of the inferior lamella of the first male pleopod is unarmed; this last character separates A. waldoschmtti sp. nov. from all its congeners.